Manajemen Dakwah Komunitas “One Ummah Movement” di Instagram - Ghirah Jihad Fie Sabilillah; Chairiawaty; Asep Ahmad Sidiq (Jurnal Riset Komunikasi Penyiaran Islam, 2025)
Abstract.This research discusses the da'wah management of the “One Ummah Movement” community on Instagram, which aims to empower young people through a social and humanitarian da'wah approach. The main problem is the application of Henry Fayol's management principles (POCCC: Planning, Organizing, Commanding, Coordinating, Controlling) to increase the effectiveness of da'wah in the digital era. This research uses a qualitative method with a descriptive approach, relying on primary data through interviews and observations, as well as secondary data from related literature. The data shows that this community utilizes Instagram as the main media with creative content such as video reels, posters, and inspirational quotes. The management process includes Planning based on social media trends, clear task organization, and cross-departmental coordination for activity implementation. In conclusion, the systematic application of management principles is proven to increase the effectiveness of community da'wah. This research contributes to digital da'wah, highlighting the importance of implementing modern management to support successful da'wah on social media. Abstrak. Penelitian ini membahas manajemen dakwah komunitas "One Ummah Movement" di Instagram, yang bertujuan memberdayakan anak muda melalui pendekatan dakwah sosial dan kemanusiaan. Masalah utama adalah penerapan prinsip manajemen Henry Fayol (POCCC: Planning, Organizing, Commanding, Coordinating, Controlling) untuk meningkatkan efektivitas dakwah di era digital. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif, mengandalkan data primer melalui wawancara dan observasi, serta data sekunder dari literatur terkait. Data menunjukkan bahwa komunitas ini memanfaatkan Instagram sebagai media utama dengan konten kreatif seperti video reels, poster, dan kutipan inspiratif. Proses manajemen mencakup perencanaan berdasarkan tren media sosial, pengorganisasian tugas yang jelas, hingga koordinasi lintas departemen untuk pelaksanaan kegiatan. Kesimpulannya, penerapan prinsip manajemen yang sistematis terbukti meningkatkan efektivitas dakwah komunitas. Penelitian ini memberikan kontribusi dalam dakwah digital, menyoroti pentingnya penerapan manajemen modern untuk mendukung keberhasilan dakwah di media sosial.